Literary Show: A Space to Share Students’ Compositions - Buitrago Escobar, Carmen Julia (Universidad Pedagógica y Tecnológica de Colombia, 2013)
AbstractThis project proposes composition and oral presentation of rhymes in a literary show as a strategy to help students incorporate pronunciation patterns in their speech, based on certain vowel sounds. This paperdescribes a small-scale research project conducted in a public school classroom located in Santa Rosa de Viterbo, Boyacá (Colombia). All the students in our research were sixth grade students1. In order to collectaccurate information, the following methods were used: a survey, an observation format, a tape recording, and students’ artifacts. Theresults proved that learners were able to create meaningful oral and written texts while practicing and improving their pronunciation.Key words: Rhymes, literary show, pronunciation patterns and vowel sounds.